TILLAGE OPERATIONS IN AGRICULTURAL LANDSCAPES IN THE CONTEXT OF GLOBAL WARMING - G. N. Gasanov; M. A. Arslanov; A. A. Aytemirov (Юг России: экология, развитие)
Aim. The aim was to identify the possibility of recycling the carbon in the atmosphere and the efficient use of photosynthetically active radiation (PAR) coming to the soil surface by means of the formation of highly natural phytocenosis in the back half of the summer and to minimize soil preparation period for the next crop in the rotation.Methods. We studied two systems of soil management in the stubble period, they cause: Firstly, CO2 emissions from the soil under the existing soil cultivation methods for crop rotation in the region. Secondly, the accumulation of CO2 in the organic mass of natural phytocenosis followed by plowing the green mass in the stage of milk-wax ripeness of the seeds – the dominants, and minimizing the period of preparing the ground for the next crop rotation.Result. According to the obtained data, it shows that a nutritious regime of soil under the winter wheat during plowing of green mass of natural phytocenosis is substantially improved compared to the tillage system. Similar findings were obtained by other researchers that justify the fact that the green manure crops, in this case natural phytocoenosis, throughout its life involves hard compound subarable soil layers in the biological cycle which is used to create organic matter.Conclusion. We provide a scientific rationale for the inexpediency of the use of existing tillage systems in agricultural landscapes, which are causing systematic destruction of weed - field vegetation during the periods free from agrocenoses.